If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(x + 5) = -5x + -3 Reorder the terms: -3(5 + x) = -5x + -3 (5 * -3 + x * -3) = -5x + -3 (-15 + -3x) = -5x + -3 Reorder the terms: -15 + -3x = -3 + -5x Solving -15 + -3x = -3 + -5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5x' to each side of the equation. -15 + -3x + 5x = -3 + -5x + 5x Combine like terms: -3x + 5x = 2x -15 + 2x = -3 + -5x + 5x Combine like terms: -5x + 5x = 0 -15 + 2x = -3 + 0 -15 + 2x = -3 Add '15' to each side of the equation. -15 + 15 + 2x = -3 + 15 Combine like terms: -15 + 15 = 0 0 + 2x = -3 + 15 2x = -3 + 15 Combine like terms: -3 + 15 = 12 2x = 12 Divide each side by '2'. x = 6 Simplifying x = 6
| 1.5-0.02x=-0.16 | | -12=-6x+4(x-5) | | 12-(6x-7)= | | 20x+42=30-4x | | 9=x^2-3x+5 | | n^2+2n-51=0 | | 3.3=x-4.6 | | x^2+11x+30.25=20.25 | | -3u+8(u-2)=9 | | 9k=-360/9 | | y^3-5y^2+2y+8=0 | | (3u+1)(6-u)=0 | | 5(w+8)=-5(3w-6)+6w | | -x^2+17=0 | | (3x-3)*x=(2x)*x | | 5m^2+3=0 | | 3log(x)-4=2 | | -7v+4(v+3)=-3 | | 1.36*x+1.78=0 | | (x+2)*(x+2+2x-8)=(x+1)*(x+1+2x-5) | | 40a+80b+90c+120d=410 | | -4(r+9)=-49 | | -16=-6+5v | | 42=18r+4(t+5) | | (-2x-6)= | | -24x-16-6x+24=2z-20+18z+26 | | -4=2y+2 | | 7(1-8v)=231 | | (2x-1)dx+(3y+7)=0 | | 2x(6+4)+(square)= | | (-2-6)= | | 71-x=165 |